HUBUNGAN DERAJAT MEROKOK DENGAN KEJADIAN HIPERTENSI PADA PRIA DI DESA X PROVINSI RIAU - Wahyu Ramadhan; Nurjamilah Nurjamilah; Ari Diansyah; Deinike Wanita Marwan (Collaborative Medical Journal, 2022)
Smoking can cause hypertension due to chemicals contained in tobacco that will cause damage to the inner layer of artery walls and cause the buildup of vascular plaque. According to the World Health Organization (WHO) states that the prevalence of hypertension will increase especially in developing countries. The causes of high prevalence of hypertension are unhealthy lifestyles, smoking habits, stress, lack of exercise, old age, and drinking alcohol. Kotabaru Seberida village is a village whose majority of men are smoking, ranging from those aged less than 20 years to old age. This study aims finding whether there is a relationship between smoking with the incidence of hypertension in men in Kotabaru Seberida Village Keritang District Indragiri Hilir Regency Riau Province. This research use analytic observational method with cross sectional approach. This study was conducted on 52 male samples aged 35-50 years. Blood pressure data were measured with mercury sphygmomanometer while smoking data was measured by questionnaire. Data were analyzed by spearman correlation test. There is a significant relationship between the degree of smoking and the incidence of hypertension in men in Kotabaru Seberida Village, Keritang District, Indragiri Hilir Regency, Riau Province with a p value of 0,000 (p <0.05) and a correlation coefficient (r) of 0.495 with a fairly strong correlation level. Conclusion: There is a significant relationship between the degree of smoking and the incidence of hypertension in men in X village Riau Province